Culture-Negative C acnes Endophthalmitis Following Implantation of a Phakic Implantable Collamer Lens. (May 2021) - Robbins, Calvin C.; Sobrin, Lucia; Ma, Kevin K.; Brouillette, Kathryn M.; Moore, Jeffrey K.
Purpose: This work describes a case of Cutibacterium acnes (formerly Propionibacterium acnes ) endophthalmitis following a posterior-chamber, phakic, Implantable Collamer Lens (ICL) surgery. Methods: A 34-year-old previously healthy woman presented with chronic unilateral iritis 8 months after bilateral ICL surgery. Original testing revealed no cause for the iritis with normal culture, serology, and autoimmune testing results. Results: Follow-up revealed C acnes by polymerase chain reaction on vitrectomy samples. Complete resolution of symptoms was achieved following removal of the implant, lensectomy, and intravitreal antibiotics. Conclusions: We believe this is the first reported case of postphakic ICL C acnes endophthalmitis. It highlights the utility of polymerase chain reaction in cases of chronic uveitis.